Evaluation of sorption of lindane on activated carbon derived from rice straw and fungal biomass of Phanerochaete chrysosporium - El-Kady, Ahmed Abdel Gawad; Jamil, Tarek Samir; Khattab, Abd El-Nasser Abd El-Hafez; Abdel-Ghaffar, Hany Hussien (Comunicata Scientiae, 2016)
Rice straw was used for preparation of activated carbon using chemical activation by impregnation with concentrated H3 PO4 followed by pyrolysis at 500 º C for 2h. Physicochemical properties were investigated by several procedures; elemental analysis, scan electron microscope and porosity characteristics. Batch experimental mode was applied for adsorption and biosorption studies. A matrix effect analysis is applied to correlate the lindane adsorption or biosorption capacity to the agitation time, initial levels of lindane and carbon dose or biosorbent concentration. The Scanning Electron Microscope images equipped with Energy-dispersive X-ray reflect the enhancement of thermo-chemical activation by H3 PO4 in increasing the porosity of AC. Sorption behavior of Lindane by Activated Carbon (AC) and Phanerochaete chrysosporium, respectively have been studied to compare the obtained results in order to consider cost effective method for agriculture wastewater treatment. The adsorption capacity and distribution coefficients were determined for the adsorption system as a function of sorbate concentration. Under the studied concentrations, the adsorption of lindane by AC and its biosorption by Phanerochaete chrysosporium match to Langmuir as well as Freundlich isotherms. Afterword, adsorption and biosorption behavior was assessed by calculation of constants for each isothermal model. Finally, Biosorption of Lindane by Phanerochaete chrysosporium showed higher and faster removal compared with AC derived from rice straw.